2002
DOI: 10.1046/j.1365-8711.2002.05226.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling methanol and hydroxyl masers in star-forming regions

Abstract: Class II methanol masers are found in close association with OH main‐line masers in many star‐forming regions, where both are believed to flag the early stages in the evolution of a massive star. We have studied the formation of masers in methanol and OH under identical model conditions for the first time. Infrared pumping by radiation from warm dust at temperatures >100 K can account for the known maser lines in both molecules, many of which develop simultaneously under a range of conditions. The masers form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
232
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(273 citation statements)
references
References 61 publications
35
232
2
Order By: Relevance
“…Theoretical works treat the 1612 and 1720 MHz lines as complementary with one line being commonly inverted while, in the same volume, the other one is in absorption. In Cragg et al (2002), it is found that 1612 MHz appears in a zone of high density (n H > 10 6 cm −1 ), for a high OH column density (N OH /ΔV > 10 11 cm −3 s) and a high gas temperature T k > 100 K. However, we presume that such conditions do not apply well to K 3-35. Although they are clearly associated with K 3-35, the 1612 and 1720 MHz lines are well separated (see position offset in Table 3 and Fig.…”
Section: Remarks On Oh Pumpingmentioning
confidence: 74%
See 1 more Smart Citation
“…Theoretical works treat the 1612 and 1720 MHz lines as complementary with one line being commonly inverted while, in the same volume, the other one is in absorption. In Cragg et al (2002), it is found that 1612 MHz appears in a zone of high density (n H > 10 6 cm −1 ), for a high OH column density (N OH /ΔV > 10 11 cm −3 s) and a high gas temperature T k > 100 K. However, we presume that such conditions do not apply well to K 3-35. Although they are clearly associated with K 3-35, the 1612 and 1720 MHz lines are well separated (see position offset in Table 3 and Fig.…”
Section: Remarks On Oh Pumpingmentioning
confidence: 74%
“…Elitzur et al 1976), and, more recently, the 1665 and 1667 MHz main lines (see e.g. Collison & Nedoluha 1994;Pavlakis & Kylafis 1996a,b;Cragg et al 2002). Nevertheless, theory is still uncertain because calculations of the OH populations in an expanding shell are a complex task with several competing processes which include: FIR (far infra red) pumping via the 2 Π 1/2 and 2 Π 3/2 ladders, NIR (near infra red) pumping from the radiation of the underlying star and circumstellar dust, line overlaps of FIR lines and collisional excitation through the 2 Π ladders.…”
Section: Introductionmentioning
confidence: 97%
“…That we find statistically different dust temperatures between sources showing excitedstate OH masers compared to the other maser types, as well as 6.7-GHz methanol masers with and without accompanying 12.2-GHz methanol masers, gives us a unique opportunity to compare with maser models (e.g. Cragg, Sobolev & Godfrey 2002. water Figure 12.…”
Section: Comparison With Maser Modelsmentioning
confidence: 77%
“…1) The proximity to the jets may indicate that the 6.7 GHz maser excitation could be favored by the outflow activity. One can speculate that the mid-infrared photons, required for pumping the 6.7 GHz masers (Cragg et al 2002), could more easily penetrate into the dense HMC gas in proximity of the outflows, taking advantage of the cavities induced by the outflowing gas. The proposed association of the 6.7 GHz masers with outflows, based on the similarity of the 3D velocities of the methanol and water masers, agrees with the results by De Buizer (2003) and De Buizer et al (2009), which find that in most cases the methanol masers are elongated parallel to jets traced by the H 2 and SiO emissions, suggesting a physical association of the 6.7 GHz masers with the corresponding outflows.…”
Section: Methanol and Oh Maser Dynamics: Jet-driven Expansion Of The Hmcmentioning
confidence: 99%